Fiber carbohydrates enhance embryogenic callus induction and double haploid production in anther cultures of three rice genotypes - YOANITA FADLILAH IRIANI; NUNUNG HARIJATI; AMINATUN MUNAWARTI (Society for Indonesian Biodiversity, 2025)
Abstract. Iriani YF, Harijati N, Munawarti A. 2025. Fiber carbohydrates enhance embryogenic callus induction and double haploid production in anther cultures of three rice genotypes. Biodiversitas 26: 3460-3468. Anther culture offers a great opportunity to produce spontaneous Double Haploid (DH) plants because the anther contains microspores that have the potential to develop into plantlets. However, the low yield of regenerative callus of Indica types (recalcitrant) compared with Japonica and Intermediate types is a problem in rice (Oryza sativa) anther culture. This study’s aim was to evaluate and analyze the effect of the addition of dietary fiber carbohydrates, namely Gum Arabic (GA) or Glucomannan (GL), at 0, 5, 10 mg L?1 in the induction medium on embryogenic callus formation in the anther culture of rice varieties Japonica (Nipponbare), Indica (Rice Kultur Jaringan [RCKJ] 24), and Intermediate (RCKJ 13). The number of anthers capable of producing callus and callus formed in the three rice varieties induced by the addition of 10 mg L?1 GA was higher than that of the treatment of GA with lower concentrations and all concentrations of GL. The addition of GA at a concentration of 10 mg L?1 significantly enhanced anther forming callus, number of callus formed, and green plantlets percentage of three rice genotypes. The highest callus induction (17% anther forming callus and 290,67% number of callus formed) was obtained from the Nipponbare genotype with the addition of 10 mg/L GA. In addition, 10 mg L?1 GA has the potential to increase the number of DH plants significantly; the number increased from 0 to 35 plants; however, it did not make a difference in the morphological characteristics of the callus formed. The addition of GL at a concentration of 10 mg L?1 also has the potential to increase the number of DH plants, although the number of DH plants only increased from 0 to 7. The addition of 10 mg L?1 GA or GL to callus induction media can be applied as an alternative to increase the number of rice double haploid plants.